Microstructure characterization and corrosion resistance evaluation of titanium anodized at different voltages - Goh, Kim Leng. (2013)
Titanium has been perceived as a good alternative for marine and biomedical applications due to its high compatibility with the human body, strong material characteristic and ability to hinder corrosion. However, at certain condition such as temperature above 80℃, titanium is still prone to crevice corrosion. As a result of its high functionality, a lot of researchers have been researching on the corrosion resistance of titanium before and after surface treatment in different environment. Different titanium alloy have also been studied to understand their corrosion resistance ability and their physical strength. As a result, this project will focus on the corrosion behavior of anodized titanium at different potentials, 50 V, 100 V and the 200 V, in sodium chloride, NaCl, solution to simulate a seawater environment.